Innovative cardiovascular casting technique features the complex malformation of berry syndrome - Wei Li; Wei Feng; Caihong Chang; Ya Liu; Xue Li; Mofeng Wang; Ling Gan; Jiaqi Zhang (BMC Pregnancy and Childbirth, 2024)
Abstract Background Prenatal diagnosis of Berry syndrome, a rare combination of cardiac anomalies including aortopulmonary window (APW), aortic origin of the right pulmonary artery (RPA), interrupted aortic arch (IAA), hypoplastic aortic arch, or coarctation of the aorta (COA), poses a significant challenge. Due to the rarity of the disease, and the limited case reports available to features the complex malformation of Berry syndrome postpartum, this article introduces an innovative approach to visually showcase this unusual disease. The proposed method provides a comprehensive display of the structural deformities, offering valuable insights for clinical practitioners seeking to comprehend this condition. Case presentation In this report, we present a case where fetal echocardiography aided in diagnosing Berry syndrome, which was later confirmed through postpartum cardiovascular casting. Our experience highlights the importance of using the three-vessel view to diagnose APW and aortic origin of the right pulmonary artery. Additionally, obtaining true cross-sectional and sagittal views by continuously scanning from the three-vessel-trachea view to the long-axis view of the aortic arch is necessary to image IAA or coarctation of the aortic arch. Conclusions Early and accurate prenatal diagnosis of Berry syndrome is feasible and our cardiovascular cast can perfectly display the microvascular morphology of the fetal heart, which may have great application prospects for postpartum diagnosis and teaching of complex cardiac abnormalities.